Integrated redox sensor and effector functions for tetrahydrobiopterin- and glutathionylation-dependent endothelial nitric-oxide synthase uncoupling. - Crabtree, M; Brixey, R; Batchelor, H; Hale, AB; Channon, K (2013)
Endothelial nitric-oxide synthase (eNOS) is a critical regulator of vascular homeostasis by generation of NO that is dependent on the cofactor tetrahydrobiopterin (BH4). When BH4 availability is limiting, eNOS becomes "uncoupled," resulting in superoxide production in place of NO. Recent evidence suggests that eNOS uncoupling can also be induced by S-glutathionylation, although the functional relationships between BH4 and S-glutathionylation remain unknown. To address a possible role for BH4 in S-glutathionylation-induced eNOS uncoupling, we expressed either WT or mutant eNOS rendered resistant to S-glutathionylation in cells with Tet-regulated expression of human GTP cyclohydrolase I to regulate intracellular BH4 availability. We reveal that S-glutathionylation of eNOS, by exposure to either 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU) or glutathione reductase-specific siRNA, results in diminished NO production and elevated eNOS-derived superoxide production, along with a concomitant reduction in BH4 levels and BH4:7,8-dihydrobiopterin ratio. In eNOS uncoupling induced by BH4 deficiency, BCNU exposure further exacerbates superoxide production, BH4 oxidation, and eNOS activity. Following mutation of C908S, BCNU-induced eNOS uncoupling and BH4 oxidation are abolished, whereas uncoupling induced by BH4 deficiency was preserved. Furthermore, BH4 deficiency alone is alone sufficient to reduce intracellular GSH:GSSG ratio and cause eNOS S-glutathionylation. These data provide the first evidence that BH4 deficiency- and S-glutathionylation-induced mechanisms of eNOS uncoupling, although mechanistically distinct, are functionally related. We propose that uncoupling of eNOS by S-glutathionylation- or by BH4-dependent mechanisms exemplifies eNOS as an integrated redox "hub" linking upstream redox-sensitive effects of BH4 and glutathione with redox-dependent targets and pathways that lie downstream of eNOS.